Effect of silencing the two major tomato fruit pectin methylesterase isoforms on cell wall pectin metabolism. (10th April 2013) - Wen, B.; Ström, A.; Tasker, A.; West, G.; Tucker, G. A.
Abstract: Post‐harvest storage is largely limited by fruit softening, a result of cell wall degradation. Pectin methylesterase (PE) (EC 3.1.1.11) is a major hydrolase responsible for pectin de‐esterification in the cell wall, a response to fruit ripening. Two major PE isoforms, PE1 and PE2, have been isolated from tomato ( Solanum lycopersicon ) pericarp tissue and both have previously been down‐regulated using antisense suppression. In this paper, PE1 and PE2 double antisense tomato plants were successfully generated through crossing the two single antisense lines. In the double antisense fruit, approximately 10% of normal PE activity remained and ripening associated pectin de‐esterification was almost completely blocked. However, double antisense fruit softened normally during ripening. In tomato fruit, the PE1 isoform was found to contribute little to total PE activity and have little effect on the degree of esterification of pectin. In contrast, the other dominant fruit isoform, PE2, has a major impact on de‐esterification of total pectin. PE2 appears to act on non‐CDTA‐soluble pectin during ripening and on CDTA‐soluble pectin before the start of ripening in a potentially block‐wise fashion.